Development of Road Safety Performance Indicators for the European Countries - Gitelman, Victoria; Vis, Martijn; Weijermars, Wendy; Hakkert, Shalom (Advances in Social Sciences Research Journal, 2014)
Purpose Safety performance indicators (SPIs) are measures reflecting the operational conditions of the road traffic system that influence the system’s safety performance. Within the EU funded SafetyNet project, SPIs were developed for seven road safety-related areas: alcohol and drugs; speed; protective systems; daytime running lights; vehicles (passive safety); roads and trauma management. The purpose was to develop meaningful SPIs that, given the available data, could be applied in Europe. Method A common procedure for the development of SPIs in each area was applied, starting with a definition of unsafe operational conditions of the traffic system and continuing with a conversion of this information into a measurable variable. Based on a literature survey, a relationship between the problem area and road safety was ascertained. Characteristics of the system's performance were analyzed aiming to select those which can be quantified. Examples of SPIs in use by different bodies and research studies were examined. Using the SPIs' concept suggested in each area, the data were collected in cooperation with national experts from 29 European countries, aiming to verify the applicability of the SPIs developed and to conduct country comparisons. Results The rationale behind the SPIs in each safety area was detailed, and the application of the developed SPIs to the European countries' comparisons was shown. For some areas, i.e. protective systems' use, sufficiently good data appeared to be available in Europe, while for other areas, i.e. speed and alcohol, data quantity and quality varied strongly. For passive vehicle safety, trauma management and roads, completely new approaches were developed for the SPIs' estimation. Conclusion Given the data are collected on a common basis, SPIs can become valuable tools in future knowledge- and data-driven policy-making in Europe.